2015
DOI: 10.1055/s-0035-1565260
|View full text |Cite
|
Sign up to set email alerts
|

Upper Cervical Epidural Abscess in Clinical Practice: Diagnosis and Management

Abstract: Study Design Narrative review. Objective Upper cervical epidural abscess (UCEA) is a rare surgical emergency. Despite increasing incidence, uncertainty remains as to how it should initially be managed. Risk factors for UCEA include immunocompromised hosts, diabetes mellitus, and intravenous drug use. Our objective is to provide a comprehensive overview of the literature including the history, clinical manifestations, diagnosis, and management of UCEA. Methods Using PubMed, studies published prior to 2015 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 44 publications
(55 reference statements)
1
46
0
Order By: Relevance
“…6,7 Preexisting hyperostotic conditions such as ankylosing spondylitis and diffuse idiopathic skeletal hyperostosis (DISH) can render the spine highly unstable following a minor fall. 8 Treating SCIs can be complicated by the presence of comorbid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Preexisting hyperostotic conditions such as ankylosing spondylitis and diffuse idiopathic skeletal hyperostosis (DISH) can render the spine highly unstable following a minor fall. 8 Treating SCIs can be complicated by the presence of comorbid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical epidural abscesses are distinctly rarer . Our review only found five cases with cervical spinal abscesses during period 2000–2017.…”
Section: Discussionmentioning
confidence: 84%
“…Cervical epidural abscesses are distinctly unusual in childhood, but they are arguably more dangerous than other SEAs. Degradation of the odontoid ligaments, with subsequent atlantoaxial subluxation or dislocation, is a risk .…”
Section: Introductionmentioning
confidence: 99%
“…Non-enhanced sagittal T2-weighted-MRI reveals that a fusiformis hyperintensity is shrinked and spinal dura sac compressed was dramatically relieved vertebral disc infection with epidural abscess is an indication for surgery. Once the patient shows any neurologic deficit, surgical decompression should be considered [8]. Although the period of antibiotic therapy for epidural abscess is still being debated, it is preferable to continue treatment for at least 4 weeks, because studies have shown a 25% rate of relapse in patients who were treated for less than 4 weeks [9][10][11].…”
Section: Discussionmentioning
confidence: 99%